2-methyl-3-buten-2-ol: A Pheromone Component of Conifer Bark Beetles Found in the Bark of Nonhost Deciduous Trees. (10th April 2012) - Zhang Zhang, Qing-He Qing-He; Schlyter Schlyter, Fredrik Fredrik; Birgersson Birgersson, Göran Göran
Abstract : Volatiles from bark of aspen, Populus tremula L. and two species of birch: silver birch ( Betula pendula Roth.) and common birch ( B. pubescens Ehrh.), were collected by direct solvent extraction and aeration of both newly cut bark chips and undamaged stems in June 1998 and subjected to GC-MS analysis. The results showed the presence of 2-methyl-3-buten-2-ol (MB), one of the two principal aggregation pheromone components of the spruce bark beetle, Ips typographus, in bark extraction samples of all the three deciduous tree species tested. In addition, one more oxygenated hemiterpene, 3-methyl-3-buten-2-one, and ( E )-3-penten-2-ol were also found in the bark extracts. Only trace amounts of MB were detected in some aeration samples of the fresh bark chips, and no MB was found from the aeration samples of undamaged stems at detectable levels. The occurrence of this compound was also confirmed in the bark of four exotic birch species: B. albosinensis Schneid., B. ermanii Cham., B. jacquemontii Spach, and B. maximowicziana Regel, but not yet in the European pines/spruces and the common yeasts. Our results raise major questions regarding the evolution, the tropospheric chemistry, and the ecological role of this hemiterpene alcohol. They also suggest that comparative studies on the biosynthetic pathways for MB in different sources would be of considerably evolutionary interest.